Effects of Hydrothermal Reaction Time on the Structure and Optical Properties of ZnO/Graphene Oxide Nanocomposites - Tran Van Khai; Le Ngoc Long; Nguyen Hoang Thien Khoi; Nguyen Hoc Thang (Crystals, 2022)
In this research, ZnO/GO nanocomposites were successfully synthesized by a simple hydrothermal method using graphene oxide (GO) and zinc acetate dihydrate (Zn(CH3COO)2.2H2O) as the reactants. The effect of the hydrothermal reaction time on the structure and optical property of the ZnO/GO was systematically investigated. The structure, morphology and chemical composition of the samples were measured by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDS) and Raman and Fourier transform infrared (FTIR) spectroscopy, while the optical properties were measured using photoluminescence spectroscopy. The synthesized products consisted of large quantities of one-dimensional (1D) ZnO nanorods (NRs), which were dispersed uniformly on the GO surface. The XRD and Raman results reveal that the ZnO NRs in the fabricated samples had a hexagonal wurtzite structure with high crystalline quality. The FESEM and TEM images reveal that ZnO NRs with an average diameter in the range of ~85–270 nm and length in the range of ~0.3–6 μm were covered with GO sheets. Additionally, it was found that the crystallographic orientation of ZnO NRs was dependent not only on the hydrothermal reaction time but also on the presence of GO in the nanocomposites. However, the addition of GO did not affect the stoichiometric ratio and the crystal structure of ZnO NRs. The room-temperature PL results indicated that, compared to those of pure ZnO, the luminescence of the GO/ZnO nanocomposites was suppressed and shifted towards a higher wavelength (red shift), which was attributed to the incorporation of ZnO NRs within the GO matrix and the formation of a C-O-Zn chemical bond in the nanocomposites. The hydrothermal technique is considered one of the best routes due to its low cost, high growth rates, low-temperature synthesis, controllable crystallographic orientation, particle size, as well as morphology.